ChemInform Abstract: Simple Access to Highly Functional Bicyclic γ‐ and δ‐Lactams: Origins of Chirality Transfer to Contiguous Tertiary/Quaternary Stereocenters Assessed by DFT. Issue 28 (July 2015) - Le Goff, Ronan; Martel, Arnaud; Sanselme, Morgane; Lawson, Ata Martin; Daich, Adam; Comesse, Sebastien
Abstract A series of bicyclic lactams is prepared by a base‐mediated reaction of hydroxyl halogenoamides with corresponding Michael acceptors.